Disability and Poverty A Global Challenge - Eide, Arne (Policy Press, 2011)
This book is about being disabled and being poor and the social, cultural and political processes that link these two aspects of living in what has been characterised as a "vicious circle" (Yeo & Moore 2003). It is also about the strengths that people show when living with disability and being poor. How they try to overcome their problems and making the best out of what little they have. This book will appeal to academics, postgraduates and policymakers in disability studies, development studies, poverty and social exclusion.